PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK (E-PROCUREMENT) PADA BUMN DI PT SEMEN BATURAJA (PERSERO) TBK PALEMBANG - Evada Dewata; Susi Ardiani; Sandrayati Sandrayati; Meilinda Mila Afsari (Politeknik Negeri Batam, 2017)
The purpose of this study is to determine the effect of GCG implementation to the procurement of goods and services performance electronically. The data of this research were collected by using interview and survey method. The total of this questionnaire is 34 sheets that spread to all staff in the procurement of goods and services department in Semen Baturaja Inc including User (the GCG secretary). The data of this research analyzed by multiple linear regression analysis using Windows SPSS version 20.0. The result of this research indicated that GCG implementation did not have a positive and significant effect to the procurement of goods and services performance electronically (E-Procurement), whereas GCG implementation has positive and significant effect to the procurement of goods and services performance electronically (E-Procurement) simultaneously.